Sympatric diversification as influenced by ecological opportunity and historical contingency in a young species lineage of whitefish - Siwertsson, Anna; Knudsen, Rune; Kahilainen, Kimmo; Præbel, Kim; Primicerio, Raul; Amundsen, Per-Arne (Evolutionary Ecology, 2010)
This article is part of Anna Siwertsons' doctoral thesis. Available in Munin at http://hdl.handle.net/10037/4566 In adaptive radiations, ecological opportunity (i.e. niche availability) is considered to be an important driver to increase phenotypic variation, but diversity may also be constrained by historical factors related to colonization events. How do ecological opportunity and post-glacial colonization history affect the phenotypic diversity in a young species lineage? We quantified phenotypic diversity by the number of co-existing morphs and a heritable morphological trait (gill raker number) in 39 European whitefish (Coregonus lavaretus) populations. Level of diversity was compared within and between three sub-arctic watercourses, and explored in relation to ecological opportunity (habitat availability and lake productivity) and colonization history (lake elevation and position). We found three main distribution patterns of gill raker number: unimodal (approximate range 20–30), bimodal (20–30 vs. 30–40), and trimodal (15–20 vs. 20–30 vs. 30–40), representing monomorphic, dimorphic, and trimorphic populations respectively. In addition, a pattern intermediate to the monomorphic and dimorphic populations was recorded in all watercourses. Polymorphism increased from west to east among watercourses, which can mainly be explained by post-glacial colonization history. Higher diversity was also observed in downstream sites within each watercourse, and increased with lake size and productivity. Our findings confirm that both ecological opportunity and historical constraints related to post-glacial colonization influence phenotypic patterns in a diverging lineage.